Evaluating Social Technology Utilization on Employee Performance Using Positivism Paradigm - Huda, Muhammad Qomarul; Irawan, Romi; Kumaladewi, Nia; Koondhar, M. Yaqoob (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2022)
Employees who are performing are assets in an organization to improve effectiveness and efficiency of work. The use of Social Technology has experienced a significant increase in the context of the company to help employee performance. This study proposes a model of employee performance measurement in terms of the use of Social Technology. The method used is a quantitative method with an extended Social Technology model. This model has seven variables: collaboration, communication, frequency of access, resource sharing, usefulness as independent, employee performance as dependent and social technology use which is the mediator. In its testing using PLS-SEM data analysis technique with SmartPLS 3.0. The test results show that there are six hypotheses tested, with five hypotheses accepted or influential and one hypothesis not accepted. Five accepted hypotheses prove that collaboration, communication, resource sharing, and usefulness have a significant effect on the use of Social Technology use and the use of Social Technology use which has a significant relationship to employee performance.